Foot health and quality of life of nursing students: an exploratory multimethod study - Bernardes, Rafael; Caldeira, Sílvia; Stolt, Minna; Correia, Nuno; Cruz, Arménio (Polytechnic Institute of Viseu, 2025)
Introduction: Foot health is often neglected in healthcare, despite its importance for nursing students, who spend long periods standing and walking.
Objective: To explore the relationship between foot health, quality of life, and knowledge among nursing students in a clinical education setting.
Methods: A sequential multimethod exploratory study was conducted with 54 students, selected through purposive snowball sampling. Assessments took place at month 0 and month 5 to analyze changes in clinical exposure.
Results: Changes in quality of life were observed, particularly in “pain/discomfort” and “anxiety/depression.” Foot problems were common, including cold feet (57.4%) and calluses (29.6%), with limited awareness of structural foot deformities. Significant correlations emerged, including a strong association between blisters and “pain/discomfort” at month 0 (0.614; p < 0.05), which weakened at month 5 (0.494; p < 0.01). Toe pain showed a very strong correlation with “pain/discomfort” (0.926; p < 0.01), while ankle pain was moderately associated with “problems performing usual activities” (0.520; p < 0.05).
Conclusion: This study highlights the intricate relationship between foot health and the quality of life of nursing students, advocating for ergonomic interventions and footwear improvements to enhance physical and mental well-being.